From Ram Tirath to Valmiki Tirath: the making of Valmiki religious identity in Amritsar - Snehi, Yogesh (Nidān, 2023)
This paper contextualises the emergence of the Valmiki Tirath as a major pilgrimage centre for the Valmiki community in contemporary Punjab. Its inauguration in 2016 has a longer history of contestation and association. Before it was officially established as a ‘Valmiki’ Tirath through an Act of the state legislature, the site was popularly known as ‘Ram’ Tirath, associating it with the legendary figure of Valmiki’s Ramayana. This was despite the site’s well-known legendary status as the abode of Sage Valmiki where Sita lived in exile with her two sons. Besides, most important shrines at the Tirath were under the control of non-Valmiki mahants, which was also the major reason for long-drawn political and legal contestation. However, the recent state recognition given to the site as a Valmiki Tirath needs to be placed within the broader contours of Valmiki social and political aspirations which can only be understood by paying attention to their demographic spread broadly in Punjab and specifically in Amritsar. This spatial context gets placed in the broader legendary association of the site with the sacred geography of Ramayana and the complexity of contemporary caste politics within which a variety of Valmiki castes—Majhabi, Chuhra, Bhangi, Balmiki—are placed. Its emergence, therefore, deviates both from the given template of the emergence of tirthas or as little traditions getting subsumed into dominant symbols.